Association of TIMI Risk Score with Angiographic Severity of Coronary Artery Diseases and In-Hospital Outcome in Patient with STEMI Undergoing Primary PCI - Howlader, Anup Kumar; Rahman, Afzalur; Momen, Abdul; Kundu, Samir Kumar; Siddiqui, Mohammad Khalilur Rahman; Roy, Sharadindu Shekhar; Kawsar, ABM Riaz; Dutta, Bijoy (Cardiovascular Journal, 2018)
Background: The Thrombolysis In Myocardial Infarction (TIMI) risk score was developed as a bedside tool to stratify STEMI patients eligible for reperfusion by their mortality risk. The TIMI risk score has shown to provide good discrimination in predicting mortality at 30 days and even up to 365 days. Methods: By purposive sampling a total of 64 consecutive patients were considered. Coronary artery disease severity was assessed by Vessels Score. The in-hospital adverse outcomes looked for were heart failure, cardiogenic shock, ventricular arrhythmia, re-infarction, stroke and death. Study subject was divided into two groups on the basis of TIMI risk score. In group I - patients with low TIMI risk score (0- 4); in group II - Patients with high TIMI risk score (≥5). Results: Multi vessel involvement were less in low TIMI group 1 (3.1%) but much greater (p<0.05) in high TIMI group 9 (28.1%). Adverse outcome was present 10(31.3%) in high TIMI group and 2(6.3%) in low TIMI group (p=0.01). Conclusion: High TIMI risk score was associated with more adverse in hospital outcome in patients with STEMI who underwent primary PCI. This study also demonstrated that the TIMI risk score carried a significant positive correlation with the coronary artery disease severity. Cardiovasc. j. 2018; 10(2): 135-139